Investigation of dual-pump fiber optical parametric amplifier using highly nonlinear dispersion shifted fiber - Abdullahi, Abdirahman Mohamud (2020)
Using multi-pump Raman amplifier provides high parametric gain over wide bandwidth with low noise figure (NF). Contrary to Raman amplifiers (RA), fiber optical parametric amplifiers (FOPA) can provide high and flat parametric gain over a bandwidth of tens or hundreds of nanometers with low-noise amplification using only 2 pumps. There are two types of FOPA: FOPA of single pump (1-P) and FOPA with dual pump (2-P). Both types of FOPA can provide adjustable gain and mid-frequency spectra, wavelength conversion, phase conjugation, pulse processing for signal processing and 0 dB noise counting. Furthermore, single pump FOPA had limited parametric gain over wide bandwidth, in addition to the difficulty to obtain an equalized power. To overcome such problem dual-pump FOPA was introduced. Performances of FOPA such as parametric gain, bandwidth, and saturation power, depend on the efficiency of the four-wave mixing (FWM) process. The higher-order dispersion coefficients affect the efficiency of FWM. Thus, this study involves determining the optimum value of the parameters in efforts to improve the spectrum of parametric amplification. The optimum values of the parameters were determined as a fiber length of 500 m, pump power P1 and P2 at input 0.75W and 1W respectively and a distance between central and zero dispersion wavelength is 1.63 nm. Meanwhile, the values of β 4 and β 6 are 6.231 × 10−5ps4/km and 1.18 × 10−8ps6/km, respectively. When the parametric gain is reduced by 3 dB the saturation power is acquired. Saturation power for λs = 1550 nm is -39dBm using the optimized parameters. Saturation power over a span wavelength from 1480 nm to 1645 nm was simulated. It shows when parametric gain increases, the saturation power reduces and vice versa.